2019
DOI: 10.1115/1.4043442
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Tremor Propagation in the Upper Limb: From Muscle Activity to Joint Displacement

Abstract: Although tremor is the most common movement disorder, there are few noninvasive treatment options. Creating effective tremor suppression devices requires a knowledge of where tremor originates mechanically (which muscles) and how it propagates through the limb (to which degrees-of-freedom (DOF)). To simulate tremor propagation, we created a simple model of the upper limb, with tremorogenic activity in the 15 major superficial muscles as inputs and tremulous joint displacement in the seven major DOF as outputs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…The high cost of thin-film multichannel intramuscular electrodes narrowed the number of patients that could be tested at this stage. Future approaches might include stimulation at multiple joints, especially more proximal ones, because tremor often propagates from proximal to distal joints [32] and this might have an effect in tremor amplitude at more distal joints.…”
Section: Discussionmentioning
confidence: 99%
“…The high cost of thin-film multichannel intramuscular electrodes narrowed the number of patients that could be tested at this stage. Future approaches might include stimulation at multiple joints, especially more proximal ones, because tremor often propagates from proximal to distal joints [32] and this might have an effect in tremor amplitude at more distal joints.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies targeted tremor at the wrist joint, and only a few studies additionally stimulated muscles or nerves controlling the elbow or shoulder. However, mechanical tremor oscillations have been proved to propagate from proximal to distal joints [59]. Therefore, focusing on just one isolated joint might be insufficient to efficiently reduce tremor, as the tremor assessed at the wrist could be a product of the oscillations produced at the elbow or shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…Puttaraksa et al have demonstrated that the phase difference in inputs to antagonist muscle groups causing tremor activation vary over a short timeframe, lending weight to the use of a closed-loop real-time system for out-of-phase electrical stimulations [35]. Mathematical models are being used to further investigate the pathophysiology of essential tremor, for example, to consider the impact of tremulous activity in different muscle groups on the tremor exhibited at each degree of freedom in the upper limb and to investigate the possibility of a combination of central and peripheral neurological factors on the generation of tremor [36,37]. Pigg et al used motion capture sensors to characterize tremor in the 7 main degrees of freedom in the upper limb of 22 essential tremor patients, finding that the degrees of freedom with the greatest amount of tremor are wrist flexion/extension and forearm pronation/supination.…”
Section: Pathophysiology Of Essential Tremormentioning
confidence: 99%